PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF ONLINE MENGGUNAKAN EASYCLASS BERBANTUAN GEOGEBRA MATERI PROGRAM LINIER - Mutrofin, Siti; Setiawani, Susi; Hussen, Saddam (Department of Mathematics Education , University of Jember, 2020)
This development research produces online interactive learning media using GeoGebra-assisted linear programming Easyclass. The purpose of this study is to describe the process and results of developing interactive online learning media using GeoGebra-assisted Easyclass linear program material. Research using the 4-D Thiagarajan model. The study was conducted at MAN 2 Jember, followed by 24 students of class XI IPA 4. The results showed a correlation value of 0.917 so that the media was declared valid with a very high category. Practicality was analyzed based on a student response questionnaire showing a percentage of 99% so that it was declared practical with excellent criteria. The effectiveness was analyzed based on the test scores of student learning outcomes after using instructional media obtained a percentage of 88% of the number of students who scored more than 75 which were categorized very well. Based on the results of data analysis, online interactive learning media using Easyclass-assisted GeoGebra linear program material meets the criteria of validity, practicality and effectiveness so that the media can be used in carrying out learning activities. Keywords: Development, Easyclass, GeoGebra, Linear Programming